Desert Truffles From Northeastern Algerian Coastal Dunes: Ecology, Identification And Symbiosis - Dafri, A.; Beddiar, A. (University of Eloued جامعة الوادي, 2017)
For several years, greater attention has been focused on desert truffles of Southern and Western Algeria. The present work is the first to be concerned on desert truffles from northeastern Algerian littoral dunes. The aim of this work is to describe northeastern Algerian truffle fields, identify collected truffle species and their symbiotic plant partner. We required two years field prospections, soil analysis, ascocarps morpho-anatomical and molecular analysis. We concluded that truffle fields share an acid sandy-loam soil and a notable abundance of many subspecies of Tuberaria gutatta (L.) Fourr. 1868, proved as desert truffles symbiotic partner. Two sandy truffle species are recorded: Terfezia arenaria (Moris) Trappe (1971) and Tuber gennadii (Chatin) Patouillard 1903. This data is the first to review knowledge on northeastern desert truffles and to report Tuber gennadii in Algeria.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: Northeaster Algeria, littoral dunes, desert truffles, Terfezia arenaria, Tuber gennadii, Tuberaria gutatta.